Frederick C. von Schiller - Posselwhite, James, 1798-1884 (engraver):::Creator::::::::::::; Kügelgen, Gerhard von, 1772-1820 (artist):::Contributor:::::::::::: (London; England; William Mackenzie)
Engraving of Friedrich Schiller by James Posselwhite based on a painting by Gerhard von Kügelgen.